Preternatural - Jeffery, Celinam; Project Muse; Project Muse. (Project Muse, 2020)
Preternatural is an exhibition catalogue published on the occasion of the exhibition "Preternatural," 9 December 2011 to 17 February 2012, Ottawa, Canada (http://www.preternatural.ca). The exhibition comprises three installation sites and 9 artists, all of whom explore the idea that art itself is a form of preternatural pursuit, in which they explore the bewildering condition of being in between the mundane and the marvelous in nature. It questions a world that understands itself as accessible, reachable, and 'knowable' and counters it with a consideration of this heterogenous proposition.
Foreword / Celina Jeffery -- Beyond nature / Celina Jeffery -- Wilderness ontology / Levi R. Bryant.
"Museum of Nature, St. Brigid's Centre for the Arts, Patrick Mikhail Gallery, Ottawa, Canada, 2011-2012."
Issued as part of book collections on Project MUSE.
Includes bibliographical references.
Description based on print version record.
Keywords: Nature in art -- Exhibitions; Electronic books; Electronic books